The mental health toll of COVID-19: significant increase in admissions to ICU for voluntary self-inflicted injuries after the beginning of the pandemic - Silvia Mongodi; Giulia Salve; Marta Ravasi; Damiano Rizzi; Matteo Mangiagalli; Valeria Musella; Catherine Klersy; Luca Ansaloni; Francesco Mojoli (International Journal of Mental Health Systems, 2023)
Abstract Background COVID-19 outbreak deeply impacted on mental health, with high rate of psychological distress in healthcare professionals, patients and general population. Current literature on trauma showed no increase in ICU admissions for deliberate self-inflicted injuries in the first weeks after the beginning of COVID-19. Objectives We tested the hypothesis that self-inflicted injuries/harms of any method requiring ICU admission increased in the year following COVID-19 outbreak. Methods Retrospective cohort single-center study comparing admissions to ICU the year before and the year after the pandemic start. All patients admitted to polyvalent ICUs—Fondazione IRCCS Policlinico S. Matteo, Pavia, Italy from February 21st, 2019 to February 21st, 2020 (pre-COVID) and from February 22nd, 2020 to February 22nd, 2021 (post-COVID) were enrolled. Results We enrolled 1038 pre-COVID and 854 post-COVID patients. In post-COVID, the incidence of self-inflicted injuries was 32/854 (3.8% [2.5–5.1]), higher than in pre-COVID (23/1038, 2.2%–p = 0.0014—relative increase 72.7%). The increase was more relevant when excluding COVID-19 patients (suicide attempts 32/697 (4.6% [3.0–6.2])–relative increase 109.1%; p < 0.0001). Both in pre-COVID and post-COVID, the most frequent harm mean was poisoning [15 (65.2%) vs. 25 (78.1%), p = 0.182] and the analysed population was younger than general ICU population (p = 0.0015 and < 0.0001, respectively). The distribution of admissions for self-inflicted injuries was homogeneous in pre-COVID along the year. In post-COVID, no admissions were registered during the lockdown; an increase was observed in summer with pandemic curve at minimal levels. Conclusions An increase in ICU admissions for self-inflicted injuries/harms was observed in the year following COVID-19 outbreak.